Impact of a post-casting homogenization treatment on the high-temperature oxidation resistance of a Cu-Ni-Fe alloy. (February 2019) - Jucken, S.; Schaal, E.; Tougas, B.; Davis, B.; Guay, D.; Roué, L.
Highlights: Cu-Ni-Fe alloy can be homogenized with an appropriate post-casting heat-treatment. Homogenisation of Cu65 Ni20 Fe15 improves its high-temperature oxidation resistance. The oxide scale consists of a CuO outer layer and a (NiO + Fe3 O4 )-rich inner layer. There is no evidence of NiFe2 O4 formation under the present oxidation conditions. Abstract: Homogeneous Cu65 Ni20 Fe15 (wt.%) alloy, which is a promising anode material for zero-carbon Al production, was successfully produced by casting followed by heat treatment at 1070 °C for 50 h. At 700 °C, the homogenization procedure increases the oxidation resistance of the homogeneous Cu-Ni-Fe alloy, as confirmed by the decreased weight gain (34% less after 20 h) and parabolic rate constant kp (by a factor of 2.5) compared to the as-cast alloy. The oxide scale formed on the homogenized alloy is thinner, more compact and coherent, consisting of a CuO outer layer and a (NiO + Fe3 O4 )-rich inner layer.